2018
DOI: 10.1371/journal.pone.0193155
|View full text |Cite
|
Sign up to set email alerts
|

A neonatal murine model for evaluation of enterovirus E HY12 virus infection and pathogenicity

Abstract: BackgroundsHY12 viruses are enteroviruses recently isolated from cattle characterized by severe respiratory and digestive disease with high morbidity and mortality in China. While the viruses exhibit unique biological and molecular characters distinct from known enterovirus E, the pathogenicity and viral pathogenesis remains largely unknown.MethodsNeonatal mice of Balb/C, ICR, and Kunming strain are infected with HY12 to determine the susceptible mouse strain. The minimal infection dose, the virus infection ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Pathogenicity for P2 and P40 HY12 virus was comparably determined using the established neonatal mouse model as described [46]. Three groups of neonatal ICR mice at the age of 3 days old were intraperitoneally inoculated with 10 8 TCID 50 of P2 and P40 HY12 virus.…”
Section: Pathogenicity Comparison For Hy12 Virus In Representative Passagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathogenicity for P2 and P40 HY12 virus was comparably determined using the established neonatal mouse model as described [46]. Three groups of neonatal ICR mice at the age of 3 days old were intraperitoneally inoculated with 10 8 TCID 50 of P2 and P40 HY12 virus.…”
Section: Pathogenicity Comparison For Hy12 Virus In Representative Passagesmentioning
confidence: 99%
“…Tissues collected from mice infected with P2 and P40 HY12 virus were processed in the procedure described previously [46]. Paraffin-embedded tissue blocks were sectioned at 5 µm using a microtome.…”
Section: Tissue Processing and Microscopic Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty 4-week-old ICR mice were purchased from the Laboratory Animal Center of Harbin Veterinary Research Institute, Chinese Academy of Agricultural Sciences (Harbin, China). The mice were randomly divided into four test groups (n = 4) (groups A-C) and a parental virus group D. They were intramuscularly inoculated with 0.2 ml containing 10 8 TCID 50 of the parental rHY12 virus or one of the three recombinant marker viruses, which were emulsified with ISA 15 (Seppic, Castres, France) adjuvant [7]. Serum samples were collected and prepared from the mice in each group by tail bleeding at 7-day intervals until 42 days after immunization.…”
Section: Immunogenicity Of the Rescued Recombinant Marker Virusesmentioning
confidence: 99%
“…In calves experimentally inoculated with an EV-E isolate, pathogenesis associated with an acute infection has been reported (25). Some studies have reported that the inoculation of experimental mice with particular strains of EV-E produced clinical symptoms as well as gross and microscopic lesions in the brain, respiratory system, and digestive system (2,26). EV-Gs are detected mainly in domestic pigs (EV-G1 to -4, -6, -8 to -15, and -17 to -19) (http://www.picornaviridae.com/enterovirus/ev-g/ev_g_seq.htm).…”
mentioning
confidence: 99%